Gender inequalities in the medical profession: are there still barriers to women physicians in the 21st century? - Pilar Arrizabalaga; Rosa Abellana; Odette Viñas; Anna Merino; Carlos Ascaso (Elsevier, 2014)
Aim: To analyze women's advancement compared with that of men and to determine whether advancement in hierarchical status differs from advancement in the professional recognition achieved by women from 1996 to 2008. Methods: A retrospective study was carried in Hospital Clínic in Barcelona. We analyzed data on temporary and permanent positions, hierarchy, promotions, specialty, age, and sex among the participants. Results: The female-to male ratio among trainee medical specialists was higher than 1 throughout the study period. After completion of specialist training, the proportion of women with temporary contracts more than doubled that of men. Less than 50% of women achieved permanent positions compared with 70% of men. For permanent non-hierarchical and hierarchical positions, the female-to-male ratio gradually decreased from 0.5 to below 0.2. Although more than 50% of trainee specialists were women, the number of female consultants remained 25% lower than that of men. In 2008, the final year of the study, the percentage of women who had achieved the grade of senior consultant was one-third that of men (29.5% of men vs 10.9% of women; p < 0.0001). Conclusions: The significant differences in medical positions held by men and women illustrate the 'leaky pipeline phenomenon', consisting of a disproportionately low number of women achieving leading medical positions. The full potential of the increasing number of women physicians will not be reached without continuing efforts to improve the hospital medicine environment.